Analisis pengaruh reformasi pajak terhadap pendapatan pajak penambahan nilai (PPN) di Indonesia - Yahya, Syafi' Ainul (Maliki Interdisciplinary Journal, 2024)
Taxes in Indonesia serve as the mainstay of the national income, supporting infrastructure development and social needs. The recent reforms in Value Added Tax (VAT) rates and tax regulations have had a significant impact, aiming to increase revenue, broaden the tax base, and create a more efficient tax system. The adjustment of the VAT rate from 10% to 11% in the Tax Harmonization Law has affected the tax structure, fairness, and efficiency. These changes encompass alterations in the VAT rate, administrative improvements, and a push for growth in the economic sector. Despite providing benefits to tax revenue and economic stimulus, continuous evaluation is necessary to ensure the sustainability and effectiveness of these reforms in supporting economic growth and investment in Indonesia.